2014
DOI: 10.1371/journal.pgen.1004141
|View full text |Cite
|
Sign up to set email alerts
|

Age, Gender, and Cancer but Not Neurodegenerative and Cardiovascular Diseases Strongly Modulate Systemic Effect of the Apolipoprotein E4 Allele on Lifespan

Abstract: Enduring interest in the Apolipoprotein E (ApoE) polymorphism is ensured by its evolutionary-driven uniqueness in humans and its prominent role in geriatrics and gerontology. We use large samples of longitudinally followed populations from the Framingham Heart Study (FHS) original and offspring cohorts and the Long Life Family Study (LLFS) to investigate gender-specific effects of the ApoE4 allele on human survival in a wide range of ages from midlife to extreme old ages, and the sensitivity of these effects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 61 publications
(95 reference statements)
4
43
0
1
Order By: Relevance
“…Further, given that the MACS includes only men, there may be sex differences in ApoE ε4 effects that could not be examined here [cf. (Beydoun, Beydoun et al 2013, Kulminski, Arbeev et al 2014)]. However, within the specific constraints of the various outcomes examined in the literature, it appears reasonable to conclude that the ApoE ε4 allele is not significantly interacting with HIV serostatus to increase risk of incident cognitive impairment or death.…”
Section: Discussionmentioning
confidence: 97%
“…Further, given that the MACS includes only men, there may be sex differences in ApoE ε4 effects that could not be examined here [cf. (Beydoun, Beydoun et al 2013, Kulminski, Arbeev et al 2014)]. However, within the specific constraints of the various outcomes examined in the literature, it appears reasonable to conclude that the ApoE ε4 allele is not significantly interacting with HIV serostatus to increase risk of incident cognitive impairment or death.…”
Section: Discussionmentioning
confidence: 97%
“…A study conducted among middle age men from nine populations showed that individuals carrying ε4 have 40% higher risk for CAD deaths compared to individuals carrying APOE3/3 or ε2 [16]. In some studies, individuals carrying ε4 have been found to be more prone to develop common coronary lesions and to have higher CAD mortality risk [11,18]. In a study carried out on 199 subjects in Adana province of Turkey, total and LDL cholesterol levels were significantly higher and HDL cholesterol level was significantly lower in CAD group compared to healthy control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…While participating in these critical processes, common apoE alleles ( ε 2, ε 3, and ε 4) can contribute significantly to the pathobiology of aging and age-related traits but this contribution can be complicated by biodemographic factors discussed above (Kulminski et al 2014; Kulminski et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…For example, studies suggest that the apoE2 allele might be protective against cardiovascular diseases (CVD) (Song et al 2004), Alzheimer disease (AD) (Corder et al 1994), and mortality (Mahley and Rall 2000). In contrast, the apoE4 allele can confer risk of Alzheimer disease (Corder et al 1993) and decrease survival chances (Christensen et al 2006; Kulminski et al 2014). …”
Section: Introductionmentioning
confidence: 99%